Reviewing risk management tools for construction projects and the implementation of project management strategies - Lungu, Able Benson (Department of Construction Economics and Management, 2020)
Purpose - The research reviewed risk management tools for construction projects and the implementation of project management strategies, in which prominence is found in the use of the integrated use of value management and risk management adapted from the Integrated Approach for Soft Value Management. The study was based on a school construction project which was used as a case study at which the researcher’s role is that of ‘Project Manager’. The project status before the study was that it was almost 100% behind schedule and experienced a wide variety of problems ranging from constant site shut-downs due to community protests, contract scope changes, poor quality workmanship and material related setbacks. The study, through literature review, considered some of the methods currently used in the built environment to mitigate unforeseen problems to construction projects and ascertained the extent to which these tools and techniques for risk management on construction projects were used. The idea behind this was to review, document and package the application of a project management strategy that would be suitably effective for resolving the problems faced on the project site. Design – The research design used in this study was the ‘Case study design’ and ‘Experimental design’ in which the ‘Action-research’ approach and ‘Embedded survey within a case study’ were employed on the construction project site, managed by the researcher in his capacity as Project Manager. This was done by organising role-players as participants in focus group workshops facilitated by the researcher where the participants interacted with the researcher and amongst themselves in an effort to identify and find possible problems affecting the project. The researcher introduced stimulating action to project management processes based on the information sourced from the literature review and data obtained from focus group workshops where the outcomes were observed, recorded, analysed and conclusions drawn. Results – The investigation results revealed that the applied management strategies in form of the approach adapted from the integrated use of value and risk management provided a conclusion that the approach was an effective and preferable technique to use in comparison with the commonly used contingencies and float for risk management on construction projects. The above processes also confirmed its relevance as an appropriate technique for risk management of most unforeseen problems which have an effect on the three constraints of time, cost and quality. A further analysis of literature reviewed, which was also supported by other studies previously undertaken, concluded that most professionals in the construction sector such as Quantity Surveyors, Construction Managers, Project Managers and Architects were aware of Value Management but rarely applied it on projects for risk management purposes. Practical Implications – Developing a standard model for the implementation of measures to deal or manage unplanned problems on a project is a challenge as most projects do not have a set model to deal with unforeseen project problems which compels the reliance on contingencies and float. However, any envisaged model must be supported by a quality control system which allows for easy implementation of interventions. The prototype step model conceptualised by the researcher is intended to enable project functionaries and project managers through its unique and easy steps to navigate through any problem which may be encountered on a project. This is regardless of the project phase in which such challenges manifest as there is no preferred model capable of resolving much more than one setback at any given time in comparison with the strategy recommended by this study, which may also be applicable to other sites where similar dynamics exist. Limitations – The study was conducted in a confined environment which required to be confirmed through longitudinal research which is broader and based on many different projects hence the results could not be generalised but only limited to the current project and further research was recommended. The single case study design was also a limitation as the results were not broad enough and were also subjective for generalisation to other project sites. Conclusion – This project management strategy in which the integrated value management approach was used has the potential of being employed as an intervention technique for unforeseen problems related to construction projects provided the processes derived from further research are documented and packaged into a process to be used as a standard model. The project management strategy has the potential to mitigate problems related to time, cost and quality only during the three phases of the project which are, initiation, planning, and implementation and excludes the closing phase to enhance project value. In iii essence, when the project cost and time are effectively managed and reduced, with enhanced quality, the result is an improved project with significant prospects of success.